A Multicenter Retrospective Review of Laterally Plated Partial Tarsal Arthrodesis in Dogs and Cats - Kaniok, Heidi; Franklin, Phil Henry; Grierson, James; Anderson, Tom; Krekis, Alex; Chung, Wai Yin; Atmaca, Kasia; Woodbridge, Nicolas (Veterinary and Comparative Orthopaedics and Traumatology, 2025)
To report complications and long-term outcomes of partial tarsal arthrodesis (ParTA) in dogs and cats.Retrospective observational study.Medical records (2016–2023) were reviewed for cases with tarsal instability treated with ParTA using laterally applied plates. Data collected included signalment, concurrent orthopedic disease, surgical technique, postoperative complications, and outcomes. Long-term outcome was assessed using the canine brief pain inventory (CBPI) and feline musculoskeletal pain index (FMPI).A total of 34 dogs and 9 cats met the inclusion criteria. The overall complication rate in dogs was 22/34 with a major complication rate of 15/34. Plantar necrosis had an incidence of 1/34. Major I complications (6/34) required partial or complete explantation, revision partial tarsal or pantarsal arthrodesis. Incidence of surgical site infection was 11/34. Minor complications occurred in cats 5/9, including mild rotational deformity, while only 1/9 cats had a major complication (rotational deformity) requiring revision surgery. Long-term follow-up was available in 21/34 dogs and 6/9 cats. Canine outcomes were excellent or very good in 14/21 dogs. The mean FMPI was 3/36 indicating very good long-term outcome.Although canine ParTA has high major complication rate, 14/21 dogs had an excellent or very good long-term outcome. Cats had a low major complication rate and very good long-term outcomes.
Keywords: canine; feline; partial tarsal arthrodesis; complications; outcome